Phytochemical Screening and Nutritional Analysis of Five Common Edible Leafy Vegetables in Southwestern Nigeria - David Ezema, Matthew; Maximillian Odoh, Ikenna; Selimot Adedeji, Odunayo; Atinuke Akinrinolu, Dorcas; Chinonso Obi, Bonaventure (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
In tropical countries, leafy vegetables are traditionally cooked and eaten as a relish together with starchy staple food. This study examined the nutritional compositions and phytochemicals of Amaranthus hybridus (‘Efo tete’), Solanum nigrum (‘Odu’), Solanecio biafrae (‘Worowo’), Telfairia occidentalis (‘Ugu’), and Corchorus olitorius (‘Ewedu’), mostly grown in western Nigeria and used in preparing staple indigenous recipes. Kjehdal method and HPLC were used for proximate composition, amino acid, vitamins and mineral analysis while alkaloids, quinones, flavonoids, tannins, phlobatannins, glycosides, cardiac glycosides, anthraquinone, saponins, terpenoids, steroids, and anthocyanides screening was carried out using standard methods. Results showed significant total soluble carbohydrates in all the leaves, with Solanum nigrum having the highest value (55.90 ± 0.10). Protein and crude fibre contents are highest in Corchorus olitorius leaves (31.85 ±0.02 and 36.02 ± 0.01 respectively) while fat and ash contents were highest in Solanum nigrum leaves (5.71± 0.01) and Telfairia occidentis (23.00±0.00), respectively. Essential amino acids such as Leucine, Lysine, Phenylalanine and Histidine were observed in appreciable values. The leaves contain a high amount of vitamin A (≥1714.70) while vitamin E and vitamin B3 are more significant in Telfairia occidentis and Corchorus olitorius, respectively. All the vegetables contain macronutrients, especially phosphorus and the above listed phytochemicals , suggesting their antioxidant potentials. The results provided evidence of the potential of these vegetables to improve nutritional and health status.